Patient satisfaction with the level of being informed about the changes in Slovenian healthcare system - Zupanc Terglav, Barbara; Selak , Špela; Vrdelja, Mitja; Kaučič, Boris; Gabrovec, Branko (Nursing in the 21st Century, 2019)
PATIENT SATISFACTION WITH THE LEVEL OF BEING INFORMED ABOUT THE CHANGES IN SLOVENIAN HEALTHCARE SYSTEM Introduction. Patients’ satisfaction has a very important role regarding reforms of the healthcare system, which aim at improvement of health and optimisation of costs. Informed patient is one of the factors which notably influences patients’ satisfaction. Aim. To determine the level of satisfaction of Slovenian residents with the current healthcare system and how well informed they are about the draft law changes to the Healthcare and Health Insurance Act, debated in public in 2017. Methods. A descriptive, non-experimental sampling method was used (snowball method). A structured questionnaire was used as a measurement tool. The number of 488 persons finished the entire online questionnaire. The data were analysed using the SPSS programme, version 21 (significance level p<0.05), and using descriptive statistics, correlation analysis, t-test and linear regression analysis. Results. Slovenian residents are fairly (un)satisfied with the current healthcare system. Waiting lines affect satisfaction with the current health care system the most, followed by the level of trust in a doctor’s decision concerning treatment and the level of respectfulness in the communication of healthcare workers with patients. Although respondents are less informed about the proposed changes, they support the draft law changes to a high degree. They perceive the information provided on the proposed changes in healthcare as relatively understandable and evaluate them positively. Television is the most important source of information on law changes in healthcare. Discussion and conclusions. Slovenian residents support the public healthcare system to a very high degree and are less in favour of private healthcare. In the future, more attention needs to be directed towards the related strategic communication and the choice of communication channels with the planned changes in healthcare.